2017
DOI: 10.21273/hortsci11499-16
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Content Differs among Microgreen, Baby Leaf, and Adult Stages in Three Cultivars of Kale

Abstract: Kale (Brassica oleracea L. and other species) is considered a rich source of important minerals. Kale at the early stage of leaf development is assumed to contain higher levels of minerals than at maturity. However, literature supporting this assumption is scarce. In this study, the concentrations of macronutrients [potassium (K), calcium (Ca), magnesium (Mg), and phosphorus (P)] and micronutrients [sodium (Na), iron (Fe), manganese (Mn), zinc (Zn), and copper (Cu)] either es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 21 publications
8
43
0
Order By: Relevance
“…No significant differences between sprouts and microgreens were detected, but the content of ash was higher in microgreens, especially for amaranths and kale ( Table 1 ). According to previous studies, sprouts, microgreens or “baby” vegetables at early growth stages are better sources of nutrients than their mature counterparts [ 21 , 22 ]. The content of ash depends on the agrotechnical techniques and growing conditions, such as soil and climatic factors, exposure to light, and the type of species or varieties [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…No significant differences between sprouts and microgreens were detected, but the content of ash was higher in microgreens, especially for amaranths and kale ( Table 1 ). According to previous studies, sprouts, microgreens or “baby” vegetables at early growth stages are better sources of nutrients than their mature counterparts [ 21 , 22 ]. The content of ash depends on the agrotechnical techniques and growing conditions, such as soil and climatic factors, exposure to light, and the type of species or varieties [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Minerals take a crucial part in versatile biological processes during plant growth stages and development, where up to 17 key minerals take part, which are transferred to human nutrition [25]. These major minerals in human diet are of utmost importance to avert any disorders, their absence affect body homeostasis and metabolism [5].…”
Section: Nitrate Concentration and Mineral Content Of Microgreens Andmentioning
confidence: 99%
“…Kyriacou et al [5] stated that potassium is the most concentrated macronutrient in microgreens followed by calcium and magnesium. In fact, potassium is abundant in plant cells and tissues, calcium partakes in coordinating plant response to internal and external stimuli and magnesium is involved in chlorophyll and protein synthesis [25]. Refering to lettuce, Weber [20] showed that hydroponically grown romaine lettuce had higher P, Mg and S and lower K, Ca and Na than mature lettuce, which is not completely in line with our results, noting that in this previous experiment mature romaine lettuce were bought from the store and the cultivar was not defined.…”
Section: Nitrate Concentration and Mineral Content Of Microgreens Andmentioning
confidence: 99%
“…Nonetheless, the nutritional profiles of mustard leaves have been limited in their analysis and quantification across different cultivars at different physiological stages. Immature plants such as microgreens and baby leaf plants have been getting popular, partially due to their intense flavor and tender texture compared to mature plants [ 17 , 18 ]. Considering their growing popularity, immature plants merit research on their nutritional value, which can assist growers in their determination of cultivation regime, as well as consumers in their food choices.…”
Section: Introductionmentioning
confidence: 99%